Clio's Lives Biographies and Autobiographies of Historians - Munro, Doug; G. Reid, John (ANU Press, 2017)
Including contributions from leading scholars in the field from both Australia and North America, this collection explores diverse approaches to writing the lives of historians and ways of assessing the importance of doing so. Beginning with the writing of autobiographies by historians, the volume then turns to biographical studies, both of historians whose writings were in some sense nation-defining and those who may be regarded as having had a major influence on defining the discipline of history. The final section explores elements of collective biography, linking these to the formation of historical networks. A concluding essay by Barbara Caine offers a critical appraisal of the study of historians' biographies and autobiographies to date, and maps out likely new directions for future work.